Two new species of the genus Afissa Dieke, 1947 (Coleoptera: Coccinellidae) from Xizang, China - Jin, Ming-Xiao; Chen, Xiao-Sheng; Wang, Xing-Min (Zootaxa, 2026)
Two new species of Afissa Dieke, 1947 are described from Xizang, China: Afissa motuoensis sp. nov. and Afissa pyramidalis sp. nov. Diagnosis, description and illustrations are provided for both species.